Pelatihan dan Pemasangan Gorunding System di UMKM GS4 Woodcraft, Malang - Abdul Muta’ali; Bambang Minto Basuki (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to improve technical aspects and workplace safety at GS4 Woodcraft MSME, Lowokwaru, Malang, through training on grounding systems and Occupational Safety and Health (OSH). Grounding systems were taught and installed to mitigate the risks of electrical current leakage and touch voltage that could endanger workers. Additionally, OSH training was provided to raise workers' awareness of the importance of workplace safety, supported by the installation of OSH posters as visual educational media. The results of the activity showed an increase in workers' understanding of the concepts and implementation of grounding systems. The installed grounding systems, as an outcome of the training, successfully met the applicable grounding system standards in Indonesia. The OSH training also had a positive impact, with workers showing increased awareness of using personal protective equipment (PPE). The strategically placed OSH posters effectively reinforced visual reminders for workers to prioritize their safety.